COVID-19 and Cardiomyopathy: A Systematic Review - Omidi, Fatemeh; Hajikhani, Bahareh; Kazemi, Seyyedeh Neda; Tajbakhsh, Ardeshir; Riazi, Sajedeh; Mirsaeidi, Mehdi; Ansari, Ali; Ghanbari Boroujeni, Masoud; Khalili, Farima; Hadadi, Sara; Nasiri, Mohammad Javad (Frontiers in Cardiovascular Medicine, 2021)
Background: Cardiomyopathies (CMPs) due to myocytes involvement are among the leading causes of sudden adolescent death and heart failure. During the COVID-19 pandemic, there are limited data available on cardiac complications in patients with COVID-19, leading to severe outcomes. Methods: We conducted a systematic search in Pubmed/Medline, Web of Science, and Embase databases up to August 2020, for all relevant studies about COVID-19 and CMPs. Results: A total of 29 articles with a total number of 1460 patients were included. Hypertension, diabetes, obesity, hyperlipidemia, and ischemic heart disease were the most reported comorbidities among patients with COVID-19 and cardiomyopathy. In the laboratory findings, 21.47% of patients had increased levels of troponin. Raised D-dimer levels were also reported in all of the patients. Echocardiographic results revealed mild, moderate, and severe Left Ventricular (LV) dysfunction present in 17.13, 11.87, and 10% of patients, respectively. Conclusions: Cardiac injury and CMPs were common conditions in patients with COVID-19. Therefore, it is suggested that cardiac damage be considered in managing patients with COVID-19.